التطرف الفكري لدى الشباب الجامعي: أسبابه ومخاطره - سطوحي، هناء رمضان أحمد (جامعة أسيوط - كلية الخدمة الاجتماعية, 2022)
إن الكشف عن جذور الإرهاب والتطرف الفكري والبحث عن أسبابه هو موضوع من أشد الموضوعات خطورة وأثرا وأجدرها بالدرس المتأني ذي النفس الطويل، ذلك لأن البشر اليوم يواجهون مشكلات الحضارة وتحديات العصر، حيث أن الإرهاب والتطرف لم يأت بالصدفة بل له أسبابه ودوافعه، ومعرفة السبب غاية في الأهمية ذلك لأن التشخيص الصحيح هو بداية العلاج الناجح، فلا علاج إلا بعد تشخيص، ولا تشخيص إلا ببيان السبب أو الأسباب، فما إذن هذه الأسباب والبواعث التي أدت إلى وجود هذا الفكر الضال وانتشاره؟ هل قد يكون لمرجع هذا الفكر أسبابا فكرية أو نفسية أو سياسية أو اجتماعية. ويعد التطرف الفكري من الظواهر الخطرة التي تهدد أمن الفرد والمجتمع بعمومه، والواقع أن تطرف بعض الشباب في آرائهم وأفكارهم واتجاهاتهم نحو بعض القضايا الاجتماعية والسياسية والدينية ظاهرة تحتل موقعها في كل المجتمعات منذ أقدم العصور، ولكنها أخذت بعدا جديدا في المجتمعات الحديثة عندما أنتج التطرف ظواهر كالعنف والعدوان على الأبرياء، والممتلكات، وفوضي الأمن في المجتمع. ومن خلال هذا البحث سيتم التعرف على مفهوم الإرهاب والتطرف الفكري وأسبابه ودوافعه وسبل المواجهة من بشكل مناسب. Uncovering the roots of terrorism and ideological extremism and searching for its causes is one of the most dangerous and influential issues and the most worthy of a long and careful study, because people today are facing the problems of civilization and the challenges of the age, as terrorism and extremism did not come by chance, but rather has its causes and motives, and knowing the cause is very important. The importance of this is because the correct diagnosis is the beginning of a successful treatment. There is no treatment except after a diagnosis, and there is no diagnosis except by clarifying the cause or causes. So what then are these reasons and motives that led to the existence and spread of this misguided thought? Could the reference to this thought have ideological, psychological, political or social reasons? Intellectual extremism is one of the dangerous phenomena that threaten the security of the individual and society in general. In fact, the extremism of some young people in their opinions, ideas and attitudes towards some social, political and religious issues is a phenomenon that has occupied its position in all societies since ancient times, but it took a new dimension in modern societies when extremism produced phenomena such as violence And aggression against the innocent, property, and chaos of security in society. Through this research, the concept of terrorism and intellectual extremism, its causes and motives, and appropriate ways of confronting them will be identified.
Keywords: التطرف الفكري -- ظاهرة الإرهاب -- التطرف الاجتماعي -- طلبة الجامعات